Donor Pretreatment with IL-1 Receptor Antagonist Attenuates Inflammation and Improves Functional Potency in Islets from Brain-Dead Nonhuman Primates. Issue 9 (September 2015) - Danobeitia, Juan S.; Hanson, Matthew S.; Chlebeck, Peter; Park, Elisa; Sperger, Jamie M.; Schwarznau, Alice; Fernandez, Luis A.
Most pancreas and islet grafts are recovered from brain-dead (BD) donors. In this study we characterized the early inflammatory response induced by brain death in pancreata and islets from nonhuman primate donors and evaluated the effect of targeted anti-inflammatory intervention in the protection of pancreatic islets prior to transplantation. BD donors were monitored for 6 h and assigned to three experimental groups: group 1: BD-untreated donors (BD-UT) ( n = 7), group 2: BD + donor pretreatment with IL-1ra ( n = 6), and group 3: non-BD animals serving as controls ( n = 7). We observed an IL-1ra-dependent reduction in the mobilization and activation of neutrophils from bone marrow and a significantly reduced accumulation of CD68 + leukocytes in the pancreas and islets after brain death induction. Donor treatment with IL-1ra significantly decreased chemokine mRNA expression (MCP-1, IL-8, and MIP-1a) and attenuated the activation of circulating neutrophils and intraislet macrophages as demonstrated by a reduction in intracellular IL-1β, IL-6, MCP-1, and MIP-1α expression. As a result, IL-1ra dramatically improved viability, mitochondrial membrane polarity, and islet engraftment in mice transplanted using a minimal islet mass. These results suggest that early immunomodulation targeting inflammation in the BD donor may represent an effective therapeutic strategy to improve islet quality and function prior to transplantation.